KONSTELASI KURIKULUM PENDIDIKAN DI INDONESIA - Rustam Abong (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Pontianak, 2015)
Curriculum in Indonesia is always related to the constellation of power, and therefore the direction and substance of the curriculum are determined by the decision of state authorities and non-state subsystems, or complying to a certain notion and concept of education. Constellation of power and complexity of curriculum can be seen in the instruction of Competency-Based Curriculum (KBK), school-based curriculum (KTSP) and 2013 Curriculum. After all, there is no guarantee that these curriculums will be able to develop students’ competency and build their character in line with the national education goals as mandated by Law No. 20/2003 on National Education System. In fact, there is nothing wrong with the curriculum; it is the fault of policy makers of education. The Indonesian people need political will of the government. Curriculum is not the only factor that determines the quality of education. Nor is it the only tool to realize the vision of education. However, curriculum can serve as a strategic device to seed the interests of power. Changes in curriculum in fact generate a strong constellation of power in the curriculum itself, especially in determining the content of education, so no wonder education in Indonesia is “subjugated” by curriculums with business and political interests.